Examining the Issues of Gender and Indigenous Knowledge in English Education Semester Courses - Mohan Singh Saud (Universitas Sembilanbelas November Kolaka, 2020)
Gender and indigenous knowledge are the contemporary cross-cutting issues to be addressed in the mainstream curriculum for enhancing inclusion and equity in higher education along with the recognition, preservation and promotion of indigenous knowledge. The issues of gender and IK are the cross-cutting subjects to be addressed in the contemporary educational discourses around the world including Nepal. Taking these issues into considering, this study critically examined and analysed the issues of addressing gender and integrating IK into the M.Ed. English courses of Tribhuvan University (TU), Nepal, along with the pedagogical practices, assessment and research. Framing on indigenous perspective with social justice, cultural capital, classroom ecology and linguicism as the theoretical lenses, this study applied qualitative study of contents analysis and an open-ended questionnaire with the teachers from TU. The study found that the course content is not much inclusive in terms of gender and indigenous knowledge. However, pedagogical practices, assessment system and research are gender and indigenous friendly as responded by the participants. Its implication is that the M.Ed. English courses of Nepal’s TU needs to address the issues of gender and indigenous knowledge for equity, inclusion and recognition of indigenous knowledge for the glocal context.